Out-of-Field Doses in Breast and Pelvic Photon Radiotherapy - Bassey Eyo Archibong; Samuel Okon Inyang; Cynthia Onyinyechukwu Igba; Isaac Bassey Ekong; Nneoyi Onen Egbe; Bede Madu; Victor Ekpo; Mary Ann Ekpo; Happiness David (International Journal of Human and Health Sciences (IJHHS), 2026)
A retrospective dosimetric analysis was conducted using treatment planning systems from two radiotherapy centers in Cross River State, Nigeria, equipped with advanced linear accelerators delivering Intensity-Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT), to investigate the levels of out-of-field radiation doses in modern photon radiotherapy and strategies to minimize exposure to normal tissues. A total of 88 patient treatment plans (41 for pelvic cancer and 47 for breast cancer) were purposively selected from archived records. These plans included a range of clinically approved techniques and varied planning target volumes (PTVs), reflecting typical clinical scenarios. Out-of-field radiation doses were evaluated at fixed distances of 2.5 cm, 5 cm, and 10 cm from the edge of the treatment field. Dose-volume histogram (DVH) data were extracted from the treatment planning system and supplemented by phantom or in vivo measurements when available.The study compared the peripheral dose distributions between treatment modalities and anatomical regions. Results showed that out-of-field doses consistently declined with increasing distance from the treatment field but remained measurable and clinically relevant even at 10 cm, indicating the persistent impact of scatter and leakage radiation. Pelvic treatments exhibited significant modality-based dose differences, particularly at 5 cm, while breast cancer treatments revealed statistically significant differences at all measured distances. VMAT treatments were generally associated with higher and more variable out-of-field doses than IMRT. Larger PTV sizes were directly correlated with increased peripheral radiation exposure. To mitigate out-of-field doses, the study recommends optimizing beam arrangements, minimizing PTV sizes when feasible, and employing shielding. Continuous dose monitoring and quality assurance practices are essential, alongside exploring emerging technologies. This study highlights the importance of treatment planning decisions in reducing unnecessary radiation exposures to the surrounding normal tissues and supports the need for individualized, safety-conscious radiotherapy strategies. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 263-269